- #1

- 59

- 0

## Main Question or Discussion Point

Given y' + ay = g(x) where y(0) =c,

also g(x) = g1, 0<=x<= xo

g(x) = g2, xo<x< infinity

for case x>xo

white

y = e^-ax Int(0->Xo){[e^aX1]g(X1)} dX1 + e^-ax Int(xo->x) [e^aX1] g(x1) dx1

I don't know why when calaulatung the case for x>Xo I have to consider the Intergration from 0 to Xo either? Can anyone tell me the answer?

also g(x) = g1, 0<=x<= xo

g(x) = g2, xo<x< infinity

for case x>xo

white

y = e^-ax Int(0->Xo){[e^aX1]g(X1)} dX1 + e^-ax Int(xo->x) [e^aX1] g(x1) dx1

I don't know why when calaulatung the case for x>Xo I have to consider the Intergration from 0 to Xo either? Can anyone tell me the answer?